Dioxygenation of cysteamine to hypotaurine at a tris(pyrazolyl)borate iron(ii) unit – cysteamine dioxygenase mimicking?12. Issue 31 (19th March 2015) - Sallmann, M.; Braun, B.; Limberg, C.
Abstract : A novel complex Tp Me, Ph Fe(SCH2 CH2 NH2 ) has been synthesized as a speculative model for ADO. Abstract : A novel complex Tp Me, Ph Fe(SCH2 CH2 NH2 ) has been synthesized as a speculative model for ADO. Indeed its reaction with O2 led to the dioxygenation of the S atom and thus to hypotaurine. This finding may allow us to draw conclusions on the constitution of the ADO active site, whose structure is still unknown.